Building high-performance knowledge institutions for water management - International Water Management Institute (International Water Management Institute, 2003)
Societies need forward-thinking knowledge institutions in the water sector to help them deal with the opportunities and crises that will arise in the future. India has some leading, high-performance knowledge institutions. But it also has many more that no longer deliver high-value thinking, insights or perspectives. Can these under-achieving institutions be transformed? How can the government, NGOs and international organizations design, build and maintain successful, highpotential institutions? Practical answers have been found in a recent review of 30 diverse Indian institutions. The review?part of an effort to improve institution-building in the water sector?found many traits that set the ?winning? institutions apart from the poor performers. First, it is the quality of an institution?s design and launch that determines its ability to lead and to be recognized as a leader in the future. Second, good operative practices?with regard to human resources, fund-raising policy, management style and core products and services?ensure an environment where innovative thinkers can excel. The research argues that a) both these aspects are vital if an institute with high potential is to flourish and b) capital investment is necessary?but not sufficient?to achieve success. Finally, the study recommends a complete relaunch of under-achieving institutions, with new NGO staff and a fresh mandate.